PROPOSAL TO IMPROVE PERFORMANCE APPRAISAL FOR LEVERAGING EMPLOYEE PERFORMANCE: THE CASE STUDY AT BPJS KETENAGAKERJAAN - Safitri, Rivanny Deva; Gustomo, Aurik (Journal of Business and Management, 2021)
Performance appraisal can be defined as one of the strategic approaches that will help a company to achieve the objective through improving the performance of the human capital that the company owns. In real practice, it has been considered as the most difficult process and most problematic HR areas for the parties involved. It indeed has been a challenge for many companies, but its program can be run in a more effective way if the management is able to fit practice, goals, and the strategy in utilizing it. In this research, an example of challenges in performance appraisal occurred in one of the biggest government entities, BPJS Ketenagakerjaan. A research conducted in which it aims to explore the performance appraisal system and the weaknesses in it. The data was collected through an in-depth interview with the Human Capital Department and the employee as users. The collected data were processed using Qualitative Coding and Analysis upon the interview result in order to understand and generate the findings. From the study, it has been indicated that in the components adopted by the company through the system, several practices have shown ineffectiveness. The issue is placed in the realization of individual appraisal data specifically in KPI measurement where all employees in the certain department have similar appraisal results. As a result, the HR function of performance appraisal that the company has can not be utilized properly. Hence, as a recommendation, BPJS Ketenagakerjaan needs to improve the performance appraisal system which focuses on fairness among employees and company’s succession cohesively through improving the cascading target process and appraisal method adjustment. Keywords : Performance Appraisal, Employee Performance, Key Performance Indicator, BPJSKetenagakerjaan.